Who am I? 52 Tuesdays, intimacy and the search for an authentic life. Issue 2 (3rd March 2016) - Murray, Virginia
Abstract: Recent research shows that young people list media entertainment as one of the sources where they find information about what they really want to know about sex and what is not taught through the school curriculum – namely, relationships and eroticism. This paper addresses the potential role that may be played by small independent alternative feature films such as 52 Tuesdays in the sexual education of young people. While 52 Tuesdays' purpose was never explicitly pedagogic, the subject matter – family relationships, sexual experimentation, sexual identity and agency, and transgender experience – situates it firmly within the concerns of contemporary young people.